2013
DOI: 10.1159/000350123
|View full text |Cite
|
Sign up to set email alerts
|

SC-535, a Novel Oral Multikinase Inhibitor, Showed Potent Antitumor Activity in Human Melanoma Models

Abstract: Background: Melanoma is considered as one of the most aggressive and deadliest cancers and current targeted therapies of melanoma often suffer limited efficacy or drug resistance. Discovery of novel multikinase inhibitors as anti-melanoma drug candidates is still needed. Methods: In this investigation, we assessed the in vitro and in vivo anti-melanoma activities of SC-535, which is a novel small molecule multikinase inhibitor discovered by us recently. We analyzed inhibitory effects of SC-535 on various melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Invasion assay was conducted as previously described with some modifications [19]. Briefly, matrigel diluted 1 : 2 in serum-free medium was coated to the top chamber of 24-well transwell plate (8 µm pore size) for 90 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Invasion assay was conducted as previously described with some modifications [19]. Briefly, matrigel diluted 1 : 2 in serum-free medium was coated to the top chamber of 24-well transwell plate (8 µm pore size) for 90 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to better mimic the process of angiogenesis induced by tumor cells in vivo and determine the inhibitory effect of SKLB-M8 on it, we performed an alginate-encapsulate B16F10 cell assay as described previously (15,24,25). A highly sensitive and relevant in vivo model was established to demonstrate the whole process of tumor angiogenesis and quantify the inhibitory action of anti-angiogenic compounds related to their antitumor activity (15).…”
Section: Sklb-m8 Inhibited Melanoma Angiogenesis In Vivomentioning
confidence: 99%
“…Yasuda et al reported that allopurinol exerts cytotoxity on human hormone-refractory prostate cancer cells in combination with tumor necrosis factor-related apoptosis-inducing ligand [ 2 ]. Many other pyrazolo[3,4-d]pyrimidine derivatives [ 3 ] were extensively explored for their potential in the treatment of cancer by targeting casein kinase 1 (CK1) [ 4 ], hepatocyte growth factor receptor (c-MET) [ 5 ], erythropoietin-producing human hepatocellular receptors B (EphB) [ 6 ], vascular endothelial growth factor receptor 2 (VEGFR2) [ 6 , 7 , 8 , 9 , 10 ], Fms-like tyrosine kinase 3 (FLT3) [ 7 , 11 ], rearranged during transfection proto-oncogene (RET) [ 8 , 10 ], epidermal growth factor receptor (EGFR) [ 10 ], MARK (mitogen-activated protein kinases) signaling [ 9 ] and Wnt (Wingless-related integration site )/β-catenin signaling [ 11 ].…”
Section: Introductionmentioning
confidence: 99%